PENGARUH SYAIR PERMAINAN PET-PET NYEUT DALAM MENINGKATKAN NILAI MORAL ANAK - Nurdiana Nurdiana; Ery Waty Ery Waty; Zulkifli Zulkifli (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2021)
Instilling moral values in children can be done through traditional games, this has been researched by Misbach (2006) from the University of Indonesia Education entitled